Pain and sociodemographic factors as moderating roles in the relationship between postoperative nausea–vomiting and recovery quality: A process macro modeling study from a nursing perspective on laparoscopic cholecystectomy patients - İlknur Tascı; Gizem Kubat Bakır (PLoS ONE, 2026)
Postoperative nausea, vomiting, and pain are common complications following laparoscopic cholecystectomy, and their impact on recovery quality remains a critical concern in surgical nursing practice. The aim of this study was to examine the relationship between postoperative nausea and vomiting and recovery quality in patients undergoing laparoscopic cholecystectomy and to evaluate the moderating roles of sociodemographic factors and pain in this relationship. A cross-sectional, multi-center, correlational design was employed using validated scales and PROCESS Macro (Model 1) moderating analysis to examine factors influencing postoperative recovery among patients undergoing laparoscopic cholecystectomy. This cross-sectional, multi-center, correlational study was conducted between December 2024 and April 2025 in the surgical units of a public training and research hospital and a foundation university hospital in Istanbul, Türkiye, with a sample of 200 patients who underwent laparoscopic cholecystectomy and met the inclusion criteria. Data were collected using the “Descriptive Information Form,” the “Quality of Recovery-40 Scale,” the “Rhodes Index of Nausea, Vomiting, and Retching,” and the “Visual Analog Scale.” Descriptive statistics, reliability analyses, confirmatory factor analysis, and moderating analyses were used in data analysis. The mean age of the patients was 52.26 ± 12.48 years, and most patients were aged 40 years or older, female, married, non-smokers, and non-alcohol users. The mean BMI was 28.89 ± 3.21. More than half of the patients reported no chronic disease, and most had a history of previous surgery. The mean VAS pain score was 6.49 ± 0.58, the mean Rhodes Index score was 15.13 ± 0.84, and the mean Quality of Recovery-40 score was 143.18. Among Quality of Recovery-40 subdimensions, the highest mean score was observed in the physical comfort domain (49.70 ± 0.53). Recovery quality was found to be negatively and strongly correlated with nausea and vomiting. The results showed that certain sociodemographic variables (gender, BMI, income level, smoking status, presence of chronic illness) and pain had significant moderating g effects in the relationship between nausea and vomiting and recovery quality, with pain having the strongest effect. Age, marital status, education level, alcohol use, and type of surgery did not show significant interaction effects. This study demonstrated that postoperative symptoms such as nausea, vomiting, and pain significantly affect recovery quality in patients undergoing laparoscopic cholecystectomy, and that this relationship is mediated by specific sociodemographic factors. These findings highlight the need for enhanced symptom management and individualized care approaches in nursing practice to improve postoperative recovery outcomes.